A comprehensive review on the antidiabetic attributes of thiazolidine‐4‐ones: Synthetic strategies and structure–activity relationships. Issue 2 (15th November 2022) - Pradhan, Tathagata; Gupta, Ojasvi; Kumar, Vivek; Sristi,; Chawla, Gita
Abstract: The thiazolidine‐4‐one scaffold has recently emerged as a potential pharmacophore having clinical significance for medicinal chemists. This heterocyclic ring has been reported to possess a plethora of biological activities, including antidiabetic activity that has inspired researchers to integrate this core with different pharmacophoric fragments to design novel and effective antidiabetic leads. The antidiabetic activity has been observed due to the ability of the thiazolidine‐4‐one nucleus to interact with different biological targets, including peroxisome proliferator‐activated receptor γ, protein tyrosine phosphatase 1B, aldose reductase, α‐glucosidase, and α‐amylase. The present review discusses the mode of action of thiazolidine‐4‐ones through these antidiabetic drug targets. This review attempts to summarize and analyze the recent developments with regard to the antidiabetic potential of thiazolidine‐4‐ones covering different synthetic strategies, structure–activity relationships, and docking studies reported in the literature. The significance of various structural modifications at C‐2, N‐3, and C‐5 of the thiazolidine‐4‐one ring has also been discussed in this manuscript. This comprehensive compilation will provide an inevitable scope for the design and development of potential antidiabetic drug candidates having a thiazolidine‐4‐one core. Abstract : The review summarizes the synthetic strategies, structure–activity relationship, and molecular docking of thiazolidine‐4‐one‐based compounds as antidiabetic agents. This review can serve as a lead for the development of novel small molecules for the management of diabetes mellitus.